الأداء البيئي لفنادق ماريوت الدولية- إلتزام اجتماعي بأداء اقتصادي متميز- - ينون, آمال (جامعة الوادي - University of Eloued, 2021)
تحقق لفنادق ماريوت الدولية في الأعوام الأخيرة عوائد مجزية أنتجتها سلسلة الممارسات البيئية التي تبنتها في أداء أعمالها. وأصبح الاهتمام بالبيئة، أحد المرتكزات الرئيسة التي أسهمت بدرجة كبيرة في بناء صورة متميزة لماريوت الدولية في سوق الضيافة العالمي باعتمادها على العميل، الموظف والمجتمعات كمفاتيح سحرية لنجاحها، والقوة المحركة لغزو الأسواق. وتهدف هذه الدراسة لتحديد العلاقة القائمة بين الأداء البيئي لفنادق ماريوت، والتزامها اتجاه المجتمعات التي تعمل فيها ومدى تأثر الأداء المالي بذلك. وتوصلت الدراسة إلى أن الأداء البيئي يؤثر ايجابيا على الأداء المالي لفنادق ماريوت، ويحسن من موقعها التنافسي في سوق الضيافة العالمي، ويزيد التزامها اتجاه المجتمعات التي تعمل فيها ضمن حلقة قائمة على مبادئ الاستدامة. In the last years, Marriott international hotels realize generous returns resulted by environmental practices that it adopted in making its business. The interest of environment is one of the principal basis which it contributed with huge degree in featured image building to marriott international in world hospitality market by adobting on costumer, employee and communities as a magic keys for it success, and the driving force to market invasion. The aim of this study is to determine the relation between environmental performance of marriott hotels, and its obligation towards communities which it worked in it and the impact of Financial performance. The study concluded that environmental performance has a positive impact on the Financial performance of marriott hotels and improves their competitive position in world hospitality market and increases their commitment towards its communities within a circle based on sustainability principles.
The environmental Performance of Marriott International Hotels - Social Obligation with Featured Economic Performance
مقال
Keywords: فنادق ماريوت الدولية، العميل، الموظف، الأداء البيئي، الاستدامة